N-alkylaryl styrylcyanine dyes as fluorescent probes for nucleic acids detection - Kuperman, M.V.; Snihirova, Y.V.; Kryvorotenko, D.V.; Losytskyy, M.Yu.; Kovalska, V.B.; Yarmoluk, S.M. (Вiopolymers and Cell, 2018)
Aim. To synthesize and characterize a series of N-alkylaryl benzothiazole styrylcyanine dyes as potential ﬂuorescent probes for nucleic acids (NA) detection. Methods. Synthesis, absorption and fluorescence spectroscopy, gel electrophoresis. Results. The modification of N-alkyl styrylcyanine by variation of aromatic moieties insignificantly affected its inherent fluorescent properties. Weakly fluorescent in an unbound state, the dyes noticeably increased their emission upon binding to dsDNA/RNA (up to 83-fold for the derivative with N-alkylbenzylamine group (Sbt1) complexed with dsDNA: with a binding constant (Kb) of 5.0×104 M⁻¹, detection limit of dsDNA in solution of 6.2×10⁻⁷ Mbp (0.4 µg)). When bound to dsDNA, styrylcyanines have moderate quantum yields (up to ~22 %). The variation of structure of the terminal aromatic group allowed to discriminate between dsDNA and RNA: the fluorescence of the Sbt2 dye with the N-alkylphenantroline group increased 14 and 55-fold, respectively. A higher discernibility of post-electrophoretic staining at low DNA concentrations (3.6 ng/lane) by the Sbt3 dye with the N-alkyldipyridyl group was observed compared to the commonly used ethidium bromide. Conclusions. Due to the sensitivity of novel styrylcyanines to NA in solution and in gel electrophoresis, they could be proposed as photostable, low-toxic and inexpensive fluorescent probes for laboratory use.